2015
DOI: 10.12659/msmbr.893950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Root Canal Preparation Using Rotary System and Hand Instruments Assessed by Micro-Computed Tomography

Abstract: BackgroundComplete mechanical preparation of the root canal system is rarely achieved. Therefore, the purpose of this study was to evaluate and compare the root canal shaping efficacy of ProTaper rotary files and standard stainless steel K-files using micro-computed tomography.Material/MethodsSixty extracted upper second premolars were selected and divided into 2 groups of 30 teeth each. Before preparation, all samples were scanned by micro-computed tomography. Thirty teeth were prepared with the ProTaper syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Continuing with the line of research, another paper compared manual preparation with ProTaper rotary files and concluded that both techniques left unprepared root canal surface and caused slight straightening of the root canal after preparation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuing with the line of research, another paper compared manual preparation with ProTaper rotary files and concluded that both techniques left unprepared root canal surface and caused slight straightening of the root canal after preparation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,4,5 Since 2012, new protocols for biomechanical root canal preparation have been developed using nickeltitanium (NiTi) instruments, whose flexibility and resistance to torsion allow their use in a continuous rotating movement; these in turn reduce the working time, operator fatigue, and the risk of operative accidents. 6,7,8,9,10,11,12,13,14,15 NiTi instruments have been developed with various geometric conformations, 8 with the most significant design difference being the taper with conicity ranging from 2% to 12%, compared to the standard 2% taper of stainless steel instruments established by ANSI/ADA in 1976 and updated in 1982. 8 NiTi rotary instruments were first commercialized in the 1990s, and since then about 700 studies have been published in journals indexed in PubMed before June 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have done segmentation by visual and automatic methods without knowing if there are differences between them in the evaluation of the images. While some studies employed visual segmentation prior to root canal volume measurement 4 , 9 , 11 , 16 , 23 , others presented only the measurements without any description as to how image segmentation was performed 10 , 25 , 29 , 30 . Alternatively, few researchers used automatic segmentation before calculating root canal volume 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In Endodontics, it is important for some studies to have a morphometric analysis of teeth for evaluating aspects such as the shaping ability of endodontic instruments, simulated root canal abnormalities, decalcification and sectioning techniques. However, some techniques can have limitations that do not fulfill the requirements for some researchers 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation